Statistical Study of EMIC Wave Propagation Using Space‐Ground Conjugate Observations. Issue 7 (12th July 2022) - Noh, Sung‐Jun; Kim, Hyomin; Lessard, Marc; Engebretson, Mark; Pilipenko, Vyacheslav; Kim, Eun‐Hwa; Johnson, Jay; Kuzichev, Ilya; Salzano, Michelle
Abstract: In the present study, we explore the observational characteristics of Electromagnetic Ion Cyclotron (EMIC) wave propagation from the source region to the ground. We use magnetometers aboard Geostationary Operational Environment Satellite (GOES) 13, the geosynchronous orbit satellite at 75°W, and at Sanikiluaq ground station (SNK, 79.14°W and 56.32°N in geographic coordinates, and L  ∼ 6.0 in a dipole magnetic field) which is located in northern Canada. Using these magnetically conjugate observatories, simultaneous EMIC wave observations are carried out. We found a total of 295 coincident and 248 non‐coincident EMIC wave events between GOES 13 and the SNK station. Our statistical analysis reveals that the coincident events are predominantly observed on the dayside. The wave normal angles are slightly higher for the non‐coincident events than for coincident events. However, the coincidence of the waves is mostly governed by the intensity and duration of the wave. This is confirmed by the geomagnetic environment which shows higher auroral electrojet (AE) and Kp indices for the coincident events. We also found that some events show high‐frequency ( f  > 0.4 Hz) wave filtering. The statistics of the high‐frequency filtered and non‐filtered wave events show that there are clear magnetic local time (MLT) and F10.7 index differences between the two groups, as well as in ionospheric electron density measurements. In addition, we also found differences in the wave properties which possibly indicate that the propagation in the magnetosphere also plays an important role in the wave filtering. Key Points: Coincidence of the Electromagnetic Ion Cyclotron wave observation is studied using conjugate space [Geostationary Operational Environment Satellite (GOES) 13] and ground (SNK ground magnetometer) observations The Coincidence of the waves is primarily dominated by wave power and duration The high‐frequency wave filtering is complicated by both magnetospheric and ionospheric wave propagation